2018
DOI: 10.3389/fnins.2018.00440
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Proteomic Analysis of Serine Hydrolase Activity in Niemann-Pick Type C Mouse Brain

Abstract: The endocannabinoid system (ECS) is considered to be an endogenous protective system in various neurodegenerative diseases. Niemann-Pick type C (NPC) is a neurodegenerative disease in which the role of the ECS has not been studied yet. Most of the endocannabinoid enzymes are serine hydrolases, which can be studied using activity-based protein profiling (ABPP). Here, we report the serine hydrolase activity in brain proteomes of a NPC mouse model as measured by ABPP. Two ABPP methods are used: a gel-based method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…The hydrolysis to N -acyl-serines might occur via multiple pathways [19]. A recent report by Van Rooden et al showed an increase in α/β-hydrolase domain-containing protein, one of the hydrolysing enzymes for N -acyl-phosphatidylethanolamine in Npc1 (-/-) mouse brains [20]. However, there is only one report about the existence of N -acyl-phosphatidylserines and N -acyl-serines in humans [21].…”
Section: Resultsmentioning
confidence: 99%
“…The hydrolysis to N -acyl-serines might occur via multiple pathways [19]. A recent report by Van Rooden et al showed an increase in α/β-hydrolase domain-containing protein, one of the hydrolysing enzymes for N -acyl-phosphatidylethanolamine in Npc1 (-/-) mouse brains [20]. However, there is only one report about the existence of N -acyl-phosphatidylserines and N -acyl-serines in humans [21].…”
Section: Resultsmentioning
confidence: 99%
“…Most of these enzymes exert their catalytic functions via nucleophilic attacking the carbonyl carbon atom of the carboxylic ester through its serine-histidine-aspartate triad [18]. Activity-based protein profiling (ABPP) is a powerful chemoproteomic strategy for assessing the catalytic activity of target enzymes in native biological systems [17][18][19][20]. In this study, we conducted an ABPP study using the desthiobiotin-fluorophosphonate (FP) probe [18] to globally assess the catalytic activity of serine hydrolases in human lung S9 (HlungS9) fractions in an effort to identify hydrolyses that can be targeted for activating an ester prodrug in the human lung.…”
Section: Abpp Of Serine Hydrolases Hlungs9mentioning
confidence: 99%
“…A mouse brain lysate was chosen as a suitable proteome for screening because it contains a wide variety of pharmacologically interesting SHs. Previous studies have identified between approximately 25 and 40 different SHs in this lysate and, conveniently, the retention of several of these on SDS-PAGE is known. Hence, the cytosolic and membrane fractions of mouse brain lysates were pretreated with compounds 4a–6f and residually active SHs were labeled with FP-Rh (Figure A). Interestingly, this competitive ABPP experiment revealed that five library members (the three triazole ureas 4f , 5f and 6f , and two NHS-carbamates 5b and 6b ) showed selective inhibition of two close-running gel bands that have previously been identified as APT-1/2 (Figure A) .…”
Section: Results and Discussionmentioning
confidence: 99%